[OP.1D.10] THE CKD273 URINARY PROTEOMIC CLASSIFIER IS NOT A MARKER OF GENERALISED VASCULAR DISEASE IN TYPE 2 DIABETIC PATIENTS WITH NORMAL RENAL FUNCTION. (September 2016) - Currie, G.; Flynn, J.; Lindhardt, M.; Mischak, H.; Rossing, P.; Delles, C.
Abstract : Objective: Microalbuminuria (MA) is a marker of diabetic nephropathy (DN) but also indicates subclinical inflammation and vascular disease, limiting its sensitivity and specificity for early prediction of DN in type 2 diabetes. A urinary proteomic classifier based on 273 peptides (CKD273) shows promise for early detection of DN; however, the influence of inflammation and subclinical vascular disease on CKD27 is unknown. Design and method: To dissect the relationship between CKD273, vascular phenotypes and inflammation without the confounding influence of MA we studied 145 normoalbuminuric patients with Type 2 diabetes participating in the PRIORITY (Proteomic prediction and Renin angiotensin aldosterone system Inhibition prevention Of early diabetic nephRopathy In TYpe 2 diabetes with normoalbuminuria) trial. Heart-rate corrected augmentation index (AIx@75) and ultrasound measurement of carotid intima-media thickness (c-IMT) were obtained. Urinary proteomic analysis was by capillary electrophoresis coupled to mass spectrometry (CE-MS). Cardiac troponin (TnT); brain natriuretic peptide (BNP); and C-reactive protein (CRP) were assessed by ELISA in a subset of 100 participants. Results: Clinical characteristics (age 61 ± 8.5; BP 135 ± 13/78 ± 9 mmHg; HbA1c 65 ± 13 mmol/mol) and markers of renal function (estimated glomerular filtration rate (eGFR) 89 ± 15 ml/min/1.73 m 2 ) and damage (urinary albumin:creatinine ratio (UACR) 7.4 ± 6.2 mg/g) were distributed within a narrow range. In contrast, CKD273 had a wider distribution (from −0.542 to 0.713) with 16 patients (11%) scoring above the threshold of 0.154 indicating risk for DN development. There was no correlation between CKD273 and vascular parameters (r = 0.13, p = 0.13 for PWV; r = −0.05, p = 0.56 for c-IMT), nor with circulating biomarkers (r = 0.05, p = 0.60 for TnT; r = 0.16, p = 0.12 for BNP; r = −0.07, p = 0.51 for CRP). PWV (9.3 vs 9.1 m/s); TnT (8.5 vs 7.4pg/ml); CRP (1.22 vs 1.19 mg/L) and BNP (56.9 vs 47.7 mg/L) were not significantly different between participants with CKD273 score above/below the mean (−0.256 ± 0.371). Forty-five (31%) patients had diabetic retinopathy and thereby a clinical diagnosis of microvascular disease. There was no association between retinopathy and CKD273 (p = 0.84). Conclusions: CKD273 is neither determined by markers of large and small vessel disease nor biomarkers of inflammation and cardiovascular risk, suggesting that it is a specific renal biomarker rather than indicating generalised vascular disease.